Penegakan Hukum Terhadap Pelaku Pencurian Di Wilayah Hukum Kepolisian Sektor Pinggir Kabupaten Bengkalis - Sari M, Ayu Novita; DM, Yusuf; Pardede, Rudi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2024)
The perpetrators of theft in Bengkalis Regency did not commit theft above Rp. 2,500,000.00 so that detention could not be carried out. The purpose of this research is to analyze how Law Enforcement Against Theft Offenders in the Legal Area of the Pinggir Police Sector of Bengkalis Regency is seen from sociological law. Based on the results of the study, it is known that Law Enforcement has not gone well because there are still criminal acts of theft, because the perpetrators of theft know that there is a minimum theft limit of Rp. 2,500,000 (two million five hundred thousand rupiah), while the stolen gold and money items range from Rp. 1,000,000 (one million rupiah) to Rp. 2,000,000 (two million rupiah). Obstacles in Law Enforcement Against Theft Perpetrators are the minimum number of police officer personnel, lack of facilities and infrastructure, and lack of public awareness of legal knowledge. Efforts to overcome these obstacles that the need for adjustment of the rule of law with the times, the need for the number of police officer personnel, the need for facilities and infrastructure, and the need for public awareness of legal knowledge.